Atmospheric remote sensing using space-based radio navigation satelities - Yahya, Mohd. Hafiz; Kamarudin, Md. Nor; Lim, Samsung; Rizos, Chris (2008)
Given that agricultural cycles, human well-being, economic growth and many societal activities are affected by climate variability, a greater understanding of critical atmospheric parameters (such as refractivity, pressure, temperature and humidity) is of paramount importance. Recently many countries have investigated the feasibility of using the space-based radio navigation satellites of the Global Positioning System (GPS) for weather and environmental studies. There are two primary methods by which GPS can be used to actively sense relevant atmospheric constituents: the ground-based atmospheric sounding method and GPS radio occultation method. Both techniques are based on using the transmitted GPS satellite radio signals to measure atmospheric profiles of refractivity. As the GPS technology is relatively new to the Malaysian weather forecasting community, this paper describes the principles underpinning both atmospheric sensing techniques. Further discussion includes the presentation of an overview of studies conducted abroad, at various scales ranging from national to global. Although GPS has the potential to improve numerical weather prediction, climate analysis and space weather forecasting, it is noted that significant research is still required in order to assess its true potential for equatorial atmospheric studies. Nevertheless, if appropriate strategies are employed during the data acquisition and data processing phases, GPS is capable of being implemented as an alternative and promising tool to remotely sense the spatial and temporal variability of the Earth’s atmosphere.